Marshallian and Jacobian externalities in creative industries - Daniel Goya (Inter-American Development Bank (IDB), 2022)
Does the growth of creative industries within a city yield both agglomeration effects (Marshallian externalities) as well as spillovers to the rest of the economy (Jacobian externalities, related to the novel combinations that can occur in cities with diversifted economic activities)? Most of the quantitative literature on creative industries investigates one or the other of these effects. Exploring both under a common framework, I ftnd signiftcant evidence of Marshallian but not of Jacobian effects. This calls for caution in the elaboration of policies meant to encourage the growth of the creative sector. The degree of specialisation in creative sectors is associated with higher sales and a higher number of ftrms in those sectors, albeit at a decreasing rate. A similar relationship is found for specialisation in creative occupations and the incomes of those workers. Though there is no evidence of spillovers from creative industries in general to the rest of the economy, analyses at a more disaggregated level could produce different results and useful insights for policy.
Keywords: R12; Z19; R58; 330; Creative industries; creative economy; Marshallian externalities; agglomeration effects; Jacobian externalities